(untitled) (AYUSHDHARA, 2017)
The term immunity is concerned with the state of being resistant or immune to foreign substances such as bacteria and other pathologic agents. The inborn resistance that is present even before first entry of a pathogen in to the host is termed as innate or natural immunity. Innate immune responses are non specific in nature. Vyadhikshamatwa as described in Ayurveda has two main arms; preventive and curative. In pediatric age group immune deficiency disorders remains the major sphere of concern. The cause can be either genetic or acquired by malnutrition and poor sanitary conditions. Ayurvedic has got a rich tradition of immune modulatory drugs viz., Swarnaprasa, Oushadhaprasas like Uramarunnu (Traditional Kerala practice), Prakaarayoga etc for boosting up innate immunity in children. Prakara yogas are formulations mentioned in Arogyarakshakalpadruma, an authentic Ayurvedic pediatric textbook, for preventing childhood illness and for boosting general immunity in children. They should be given as a schedule in different age groups periodically from birth up to12 years of age. Just as a fence that protects the house from various enemies, Prakara yogas protect the child from various ailments.